ERP SYSTEM IMPLEMENTATION AS AN IMPORTANT STAGE OF THE COMPANY'S DEVELOPMENT - S.V MUZALEV; E.S ZHARIKOV (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
Corporate governance technologies play a critical role in building a competitive and profitable enterprise. After all, they combine the receipt, accounting, storage and processing of information, help to reduce the timing of all business processes, provide timely analysis and forecasting of the economic activity of the enterprise. Communication of work with scientific programs, plans, topics. The master's thesis for the master's degree was carried out at the University in accordance with the plans of scientific research of the Department of Management on the topic "Business Analytics". The role of the author is to disclose the essence of corporate management technologies, their analysis at the enterprise in the context of international business and proposals for improving corporate technologies at the enterprise. In the ERP system, all data is stored in a single information database, which contributes to the rapid search for the necessary data and the rapid response of management personnel to changes, as well as the development of management decisions based on up-to-date and reliable information. ERP systems have mechanisms for integrating structural divisions, so that management personnel can monitor and coordinate the work of each financial responsibility center and each structural division in both regular and critical situations. For successful business development, improving the competitiveness of the enterprise, timely and adequate response to numerous threats, the company manager must rely not only on highly qualified personnel who can offer optimal solutions to the problem, but also on information technologies containing analytical tools that allow assessing the consequences of each decision. The problem of "survivability" in Russia of the technocentric approach in management is connected, among other things, with the fact that often the management of the enterprise does not use IT technologies that allow choosing the most optimal solution to the problem from several available ones. The fear of making a mistake when making a management decision makes the manager ignore suggestions for solving problem situations coming from subordinates, and rely on their own knowledge, experience and intuition.